Long term effects of gluten-free diet in non-celiac wheat sensitivity. Issue 1 (February 2019) - Tovoli, Francesco; Granito, Alessandro; Negrini, Giulia; Guidetti, Elena; Faggiano, Chiara; Bolondi, Luigi
Summary: Background & aims: Information about the clinical outcome of patients with non-celiac wheat sensitivity (NCWS) treated with gluten-free diet (GFD) derive from studies assessing the symptom response in the first few weeks of treatment. We aimed to evaluate the clinical response to the GFD and the quality of life (QoL) of NCWS patients in the long term. Methods: Forty-four NCWS (diagnosed according to the Salerno criteria) participated in the study. Participants rated their symptoms according to a 0–10 scale patients and filled in a QoL questionnaire (CDQ) before the beginning of the GFD and during a follow-up evaluation performed after at least one year. To assess the reliability of the questionnaire we also included a control group of 43 matched patients with celiac disease (CD). Results: Upon diagnosis, NCWS patients had a high prevalence of intestinal and extraintestinal symptoms. Also, most symptoms were described as severe and the QoL questionnaire showed high scores. On follow-up, both prevalence and severity of the most common symptoms were significantly reduced. However, persistent intestinal and extraintestinal symptoms of mild severity were found in 65.9 and 72.7% of NCWS patients. In comparison, in the CD group, the prevalence was lower (32.6 and 23.2% respectively) and consistent with previous studies. The analyses of the determinant of QoL showed that, upon diagnosis, NCWS patients had higher scores in the CDQ "gastrointestinal symptoms" (p < 0.001), "emotional aspects" (p < 0.001) and "social problems" (p < 0.001) subclasses compared to CD patients. After the GFD, NCWS and CD patients shared similar scores in all of the subclasses. Conclusions: A significant proportion of NCWS patients still complains of intestinal and extraintestinal symptoms, even if significantly attenuated by the GFD, even years after the diagnosis. A comprehensive nutritional evaluation of these patients is required to further improve their symptoms and their QoL.